Probiotics in urolithiasis - Kusz, Monika; Alzubedi, Adam; Popiołek, Joanna; Konopelko, Michał (Journal of Education, Health and Sport, 2018)
Urolithiasis is considered a civilization disease. The prevalence is estimated at 5-20% of the population. There are many litogenesis risk factors such as hypercalciuria, hypophosphaturia, low urine pH or increased excretion of oxalates with urine - a condition called hyperoxaluria which is a major risk factor for renal stones. Oxalate urolithiasis can be caused by defects in oxalates metabolism, excessive intake in the diet or increased intestinal absorption of oxalates. The reason of hyperoxaluria might be a genetic defect (primary hyperoxaluria) or excessive consumption due to improper diet (secondary hyperoxaluria). Human intestinal flora plays an important role in oxalates metabolism. Described in the 1980s Oxalobacter formigenes, inhabiting the human gastrointestinal tract is known for contributing to decrease the excretion of oxalates with urine and consequently, reduce the risk of recurrence of kidney stones. Other known bacteria which have a beneficial effect on the metabolism of oxalates include Lactobacillus, Enterococcus faecalis, Providentia retgerri. These bacteria may be useful in the future treatment of calcium oxalate urolithiasis.